Unveiling the Intrinsic Structure and Intragrain Defects of Organic–Inorganic Hybrid Perovskites by Ultralow Dose Transmission Electron Microscopy. Issue 17 (17th March 2023) - Yang, Chen‐Quan; Zhi, Rui; Rothmann, Mathias Uller; Xu, Yue‐Yu; Li, Li‐Qi; Hu, Zhi‐Yi; Pang, Shuping; Cheng, Yi‐Bing; Van Tendeloo, Gustaaf; Li, Wei
Abstract: Transmission electron microscopy (TEM) is a powerful tool for unveiling the structural, compositional, and electronic properties of organic–inorganic hybrid perovskites (OIHPs) at the atomic to micrometer length scales. However, the structural and compositional instability of OIHPs under electron beam radiation results in misunderstandings of the microscopic structure–property–performance relationship in OIHP devices. Here, ultralow dose TEM is utilized to identify the mechanism of the electron‐beam‐induced changes in OHIPs and clarify the cumulative electron dose thresholds (critical dose) of different commercially interesting state‐of‐the‐art OIHPs, including methylammonium lead iodide (MAPbI3 ), formamidinium lead iodide (FAPbI3 ), FA0.83 Cs0.17 PbI3, FA0.15 Cs0.85 PbI3, and MAPb0.5 Sn0.5 I3 . The critical dose is related to the composition of the OIHPs, with FA0.15 Cs0.85 PbI3 having the highest critical dose of ≈84 e Å −2 and FA0.83 Cs0.17 PbI3 having the lowest critical dose of ≈4.2 e Å −2 . The electron beam irradiation results in the formation of a superstructure with ordered I and FA vacancies along <110>c, as identified from the three major crystal axes in cubic FAPbI3, <100>c, <110>c, and <111>c . The intragrain planar defects in FAPbI3 are stable, while an obvious modification is observed in FA0.83 Cs0.17 PbI3 under continuous electron beam exposure. This information can serve as a guide for ensuring a reliable understanding of the microstructure of OIHP optoelectronic devices by TEM. Abstract : Transmission‐electron‐microscopy‐based characterization techniques are expected to play a significant role in revealing the structural, compositional, and electronic properties of organic–inorganic hybrid perovskite materials and optoelectronic devices. However, perovskites are unstable and highly sensitive to electron beam radiation. This paper has outlined key guidelines for imaging the intrinsic structure of organic–inorganic hybrid perovskite materials.